Co-occurrence of decrements in physical and cognitive function is common in older oncology patients receiving chemotherapy. (October 2020) - Utne, Inger; Cooper, Bruce A.; Ritchie, Christine; Wong, Melisa; Dunn, Laura B.; Loyland, Borghild; Grov, Ellen Karine; Hammer, Marilyn J.; Paul, Steven M.; Levine, Jon D.; Conley, Yvette P.; Kober, Kord M.; et al.
Abstract: Purpose: Older adults receiving cancer chemotherapy are at increased risk for decrements in physical (PF) and cognitive (CF) function. Objectives: Study identified subgroups of patients with distinct PF and CF profiles; risk factors associated with subgroup membership; and impact of subgroup membership on quality of life (QOL). Methods: In 366 older oncology patients, PF and CF were assessed using the Physical Component Summary (PCS) of the SF-12 and Attentional Function Index, respectively. Latent profile analysis was used to identify subgroups of older patients with distinct PF/CF profiles. Results: Three distinct PF/CF profiles were identified (i.e., Very Low PF + Moderate CF (15.6%); Low PF + Low CF (39.3%), Normal PF + Normal CF (45.1%)). Compared to the both Normal class, patients in the other two classes had a lower functional status, a worse comorbidity profile, and were less likely to exercise on a regular basis. Compared to the Both Normal class, patients in the Both Low class were less likely to be married/partnered, more likely to live alone, less likely to be employed, and more likely to report depression and back pain. Compared to the other two classes, patients in the Both Low class had a lower annual household income and were receiving chemotherapy with a worse toxicity profile. Conclusion: First study to use a person-centered analytic approach to identify subgroups of older adults with distinct PF/CF profiles. Fifty-five percent of the older adults had statistically significant and clinically meaningful decrements in both PF AND CF that had negative effects on all aspects of QOL. Highlights: Older oncology patients have deficits in both physical and cognitive function. Comorbidities increase the risk for decrements in physical and cognitive function. Depression was associated with decreases in physical and cognitive function.